The Ambiguity of Norms in Legal Protection for Advocates and the Problem of the Limits of Good Faith in the Criminal Justice System - Arih Wira Suranta; Indah Kusuma Wardhani (Asian Journal of Social and Humanities, 2026)
Legal protection for advocates is a fundamental prerequisite for the realization of fair trials, particularly in ensuring the independence of the defense function within the criminal justice system. The regulation of advocate immunity rights in Article 149 paragraph (2) of Law Number 20 of 2025 concerning the Criminal Procedure Code normatively guarantees that advocates cannot be prosecuted criminally or civilly in the exercise of their profession, but this protection is limited by the phrase "good faith," which has no operational definition or objective parameters. This gap creates normative ambiguity that generates tension between protection and restriction, with implications for legal uncertainty and the potential criminalization of advocates arising from disparate interpretations by law enforcement officials. This study aims to analyze the normative construction of advocate immunity, examine the conceptual problems of "good faith" as the boundary of immunity, and evaluate its implications for legal certainty and professional independence. The method employed is normative juridical research with statutory, conceptual, and comparative approaches. The research findings indicate that the absence of measurable indicators for assessing "good faith" leaves room for excessive discretion and weakens the effectiveness of advocate protection. This study proposes a reconstruction of the concept of "good faith" through the formulation of an operational definition grounded in the advocacy function, the use of professional standards and codes of ethics as objective parameters, and regulatory harmonization to strengthen legal certainty within the criminal justice system.